ANDROID BASED WIRELESS LIGHT CONTROLLER - Irip, Charrain Cintrai (IRC, 2019)
Android based wireless light controller is a system that provides a a solution to ease people’s daily activities. The system also offers a better security and safety for addressing the conventional light system. In order to study the awareness of the general public on this subject matter, a set of online questionnaires using Google Form has been distributed among students of Universiti Teknologi PETRONAS and also outsiders. The results from the questionnaire are used to study the awareness on energy efficiency, safety and security among the public. The Rapid Application Development (RAD) has been adopted as the methodology to develop the prototype. In this project, a Bluetooth has been chosen over Wi-Fi due to its feature on multifactor authentication, hence, be able to provide a more enhanced security. The final deliverable is a working prototype developed using MIT App Inventor to control lights in a wireless manner for the home environment.